Examining the Moderating Effect of Financial Constraint on Tax Compliance: A Sequential Explanatory Design Study on Malaysian Tax Professionals - Nivakan, Sritharan; Salawati, Sahari; Sharon, Cheuk Choy Sheung; Ahmad Syubaili, Mohamed (Universiti Pendidikan Sultan Idris, 2022)
The COVID-19 Pandemic has created a new normal across the world regardless of its economic status. The financial condition of individuals as well as corporate sectors had put them in a situation to alter their decision-making in many aspects. This paper is aimed to examine the moderating effect of financial constraints on the personal tax compliance of tax professionals who work for Malaysian businesses. It is assumed in the previous studies related to corporate tax compliance that a tax professional's personal tax compliance behaviour may influence corporate tax compliance decision-making. Therefore, this study tests their tax compliance behaviour. For that sequential explanatory design has been employed. The preliminary data was collected from the tax professionals of Malaysian businesses and then supplementary data was collected from tax experts such as tax agents, tax officers, and tax scholars. 392 responses from tax professionals and 9 responses from tax experts were analyzed using structural equation modeling. The finding reveals that the financial constraints of Malaysian tax professionals moderate their personal tax compliance. The outcome produces a piece of empirical evidence that tax policymakers should consider and implies the importance of accrual basis accounting in tax management.